Usefulness of virtual reality in the management of pain associated with venepuncture: a multicentre randomized clinical trial - Raquel Gil Piquer; Yolanda Mañes Jiménez; María España Marí; Anna Peris Peris; Purificación Solanes Donet; Nieves García Lledó; Natividad Pons Fernández (Anales de Pediatría (English Edition), 2024)
Objective: To assess the efficacy of virtual reality (VR) in reducing pain and anxiety associated with scheduled blood draws. Material and methods: We conducted multicentre randomized clinical trial in both primary care and hospital settings. The study included children aged 7–12 years undergoing blood extraction procedures between March and October 2022. The intervention group used headsets, and the control group received usual care. Pain was assessed using the visual analogue scale and anxiety using the Groningen Distress Scale. The anxiety of the nursing staff and family satisfaction were assessed with numerical scales ranging from 1 to 10. Results: The study included 83 patients: 40 in the control group and 43 in the VR group. The median age was 10 years (range, 7−12 years). In the VR group, 83.7% of the children reported mild pain, compared to 57.5% in the control group (P = .012). Also, 93% of children in the VR group showed calm or mild anxiety (score, 1−2), compared to 72% of the control group, a difference that was not statistically significant (P = .08). Family satisfaction was higher in the RV group (score ≥ 9/10: 93% of RV group vs 72.5% of control group; P = .026). The nursing staff anxiety score was less than 5 in more than 90% of cases, with no differences between groups (P = .13). Conclusion: The use of VR during venepuncture decreases the pain perceived by children and increases the satisfaction of their families. Resumen: Objetivo: Comprobar la eficacia de la realidad virtual (RV) en la disminución del dolor y ansiedad asociados a extracciones sanguíneas programadas. Material y Métodos: Ensayo clínico aleatorizado multicéntrico realizado en atención primaria y hospitalaria. Se incluyeron los pacientes de 7 a 12 años que acudieron entre marzo y octubre de 2022 a realizarse una extracción sanguínea programada.En el grupo intervención se utilizaron gafas de RV y en el grupo control cuidados habituales. Se evaluó el dolor mediante la Escala Visual Analógica y la ansiedad mediante la Groningen Distress Scale. Se evaluó la ansiedad de enfermería y la satisfacción de los familiares, mediante escala numérica del 1 al 10. Resultados: Se incluyeron 83 pacientes: 40 en el grupo control y 43 en el grupo RV. La mediana de edad fue de 10 años (rango de 7 a 12). El 83,7% de los niños en el grupo RV refirió dolor leve, frente al 57,5% del grupo control (p = 0,012). El 93% del grupo RV mostró calma o ansiedad leve (puntuación 1−2), frente al 72% del grupo control, aunque sin diferencias estadísticamente significativas (p = 0,08).La satisfacción de los familiares fue mayor en el grupo RV (≥9/10: 93% de RV vs 72,5% de controles, p = 0,026). La ansiedad de enfermería fue < 5 en más del 90% de los casos, sin diferencias entre grupos (p = 0,13). Conclusiones: El uso de RV durante la venopunción disminuye el dolor percibido por los niños y aumenta la satisfacción de sus familiares.